2022
DOI: 10.1177/07356331221101081
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a Scaffolding-Based Mindtool for Gamified Learning Classrooms

Abstract: A scaffolding-based mind tool was designed to allow teachers to easily create lesson plans for in-class gamified activities and to embed various scaffoldings in the lesson plan design. The purpose of this study was to investigate the learning outcomes of a scaffolding-based mind tool integrated with gamified learning activities applied to a science course. The study was conducted to investigate students' learning outcomes, flow, and qualitative feedback on the scaffolding-based mind tool. A total of 134 high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It is also suggested that teachers can use scaffolding strategies in gamification activities to provide feedback and guidance to students when they encounter cognitive challenges and to positively influence students' motivation to learn mathematics. Several previous studies have also found positive benefits for learners from the simultaneous use of multiple scaffolds in the gamified learning activities (e.g., Hou & Keng, 2021;Chen et al, 2022). It is suggested that the technologyoriented gamification mechanism can be combined with mobile devices to provide multi-dimensional scaffolding in order to promote motivation and cognitive thinking in distance learning.…”
Section: Suggestions and Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also suggested that teachers can use scaffolding strategies in gamification activities to provide feedback and guidance to students when they encounter cognitive challenges and to positively influence students' motivation to learn mathematics. Several previous studies have also found positive benefits for learners from the simultaneous use of multiple scaffolds in the gamified learning activities (e.g., Hou & Keng, 2021;Chen et al, 2022). It is suggested that the technologyoriented gamification mechanism can be combined with mobile devices to provide multi-dimensional scaffolding in order to promote motivation and cognitive thinking in distance learning.…”
Section: Suggestions and Implicationsmentioning
confidence: 99%
“…1. During the activity, teachers used the Mind Tool for Gamified Learning (MTGL) (Chen et al, 2022) to plan learning progress and to provide points and scaffolding. Students used MTGL to get learning information and scaffolding, Google Meet to communicate, and Google Jamboard to piece together boards and assemble them to complete the layout.…”
Section: Online Gamified Learning Activity With Multi-representationa...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following completion of an assignment unit, it is important to also consider the provision of feedback. In the context of gamified activities, feedback can be provided both during (e.g., failure/replay, provision of hints/help) and after the game (e.g., reflection moments, watching others playing, review of recent activity) [82]. The nature of feedback can take multiple forms (e.g., text, audiovisual) and can be used either in isolation or as a combination [83].…”
Section: Assessment/feedbackmentioning
confidence: 99%
“…Although there are numerous studies related to game-based learning [12,13], how to use these findings in teaching practices requires more research and scrutiny. For this reason, gamified interventions are beginning to be implemented in social education to complement Societies 2023, 13, 203 2 of 11 actions outside and inside the classroom [14].…”
Section: Introductionmentioning
confidence: 99%